Prenatal Maternal Stress Due to Repeated Exposure to Cold Environment Affects Development of Catecholamine Neurons in Rat Offsprings - Ikemoto, Keiko; Uwano, Teruko; Ono, Taketoshi; Nishijo, Hisao (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Using 8-day-old pups and tyrosine hydroxylase (TH) immunohistochemistry, we investigated the influence of maternal recurrent cold stress (RCS) on catecholamine neuron development in offsprings. Between day 10 to 20 day following fertilisation, RCS was loaded into pregnant rats. The frontal and cingulate cortices tended to contain fewer TH-immunoreactive (-ir) fibers, and density of TH-ir varicosities with a large size (more than 7 \(μ\)m in diameter) was significantly (p<0.05) lower in rats prenatally exposed to RCS than controls. In prenatal RCS rats, locus coeruleus neurons had decreased TH immunoreactivity than controls. In the medullary C1/A1 catecholaminergic field, RCS rats had smaller TH-ir neurons and fewer TH-ir fibers, however the differences were not significant. We found no variations in TH-ir structures between the two groups in originating and projection regions of the midbrain dopaminergic system. Prenatal RCS hampered development of catecholaminergic neurons, particularly noradrenergic neurons in pups, according to these studies.